Ensino programado para o planejamento de aulas de matemática de ensino fundamental - Médici, Arthur Damião (Universidade Federal de São Carlos, 2016)
Lesson planning is part of the teaching and learning process. Given the effects of planning on teacher behavior, some initiatives use lesson planning as teacher training procedure. A lesson plan - desired product of the planning process - highlights key aspects of teaching conditions within a lesson and the information presented in it may vary according to the function of that plan. A lesson plan is a tool that ensures the registration of practice and can serve to continue improving these practices. Problems occur when the conditions given in a lesson plan do not match - or correspond in an oversimplified way to - the actual conditions created in class. Investigations conducted in Brazil give evidence that the practice of preparing lesson plans is often seen as bureaucracy to be fulfilled by the institution. In addition to this, in some institutions, teachers are responsible for the implementation of lesson plans already drawn up, however, planning lessons is necessary since teachers deal with different students in different educational situations, which requires that the teacher is able to plan an effective class for each school condition. Mathematics is a subject of increasing importance in national and international curricula as it constitutes the basis for all scientific and technological development in various areas of knowledge. There is requirement that mathematics be taught in a way that makes sense to the reality of the students, however it evolves as science increasingly abstract. Therefore, teachers should be prepared to create teaching conditions that make sense for their apprentices. The teaching program is a method that allows the identification and description of relevant behavior and educational conditions to promote them and evaluate them. Through educational programming was possible to identify relevant behaviors for teachers, more specifically, behaviors related to the planning of teaching conditions. Through educational programming it is possible to identify behaviors relevant to plan lessons taking into account relevant aspects of teaching conditions in which the teacher must plan. Thus, this study aimed to develop and test the effectiveness of an educational program for math teachers of elementary school whose purpose is to plan lessons. For the preparation of the program have used the mathematics curriculum of primary education in the state of São Paulo, instructional self material development of educational programs, articles indicating effective practices for teaching and learning and teaching materials in mathematics with examples of activities . Two employees were consulted one with understanding in educational programming and other training of mathematics teachers. The preparation of the program involved the justification of the relevance of the program, the description of the terminal objective, analysis of the ultimate goal in intermediate goals, description of intermediate goals in its functional parts, the description of the teaching conditions, the drafting of background papers of teaching units and the drafting of educational activities. All products have been sent to reviewers for comments and improvement. In addition, the self-correcting feature of the programming process, products were enhanced as new products were developed. Behavior was proposed as a terminal for the program of this study - to prepare math lesson plan - and three intermediate behaviors were identified in the first level - propose teaching objectives, specify teaching and specify assessment procedures. Each of the intermediate behaviors on the first level was the objective of each of the teaching units of the program. The elaborate program consists of a pre-test, self initial assessment, three teaching units, a post-test and self final evaluation. It has auto format instructional - so you do not need a mediator to be applied - and, therefore, has some features to help the learner to realize their own learning as early examples, check fields, display fields and response resubmission , response checklists and self assessments. For the analysis of program effectiveness, 5 undergraduate students in mathematics and three mathematics teachers participated in the application. Participants performed all activities proposed by individually program at times of their convenience. After each participant terminate implementation of the program, an interview was conducted opinion. Programmer and an external evaluator examined the performance in pre- and post-tests. Programmer evaluated the performance in educational units. They were also examined the reports on self assessments and interviews about the program. As a result of analysis of its effectiveness, it is possible to observe an improvement of the performance of pre to post in all cases and the most obvious improvements were E3 and D2 - both are the worst performing in the pretest - and less expressive E1 and E5 - E1 having higher performance in the pretest and E5. performance close to the average. Items related to the proposition teaching objectives had greater improvement. The opposite occurred with items related to assessment procedures specification. E3 and D2 that have more obvious improvements in the pre-test also had the best performance in teaching units. E1 had worse performance in teaching and low improvement in pre- to post-test. The best performances were observed for the unit 3 (evaluation) and the worst for the unit 1 (teaching objectives). Participants, in general, declared better prepared to plan lessons with the exception of E2 and D1 which had slight decline. E1, E3 and D3 reported higher increase in / out being that E3 had high improvement pre / post-test and high performance in teaching units. The main positive aspects indicated by the participants is that the program offers additional support to that provided by the undergraduate degree, the sequence of the program corresponds to that in which planning should occur and that the texts and activities present examples applicable to the reality of teachers. The main suggestions made by participants to program improvement are providing additional examples of lesson plans, show less answers to reading questions, offer the program as a classroom course to be exchange of ideas and invest the program's direction for students of graduation. The auto format instructional program is used in different cases to promote behaviors in professionals in different areas, often resulting in increased performance of participants self instructional program when compared to the traditional education system - in which the instruction is provided by a mediator. There are differences between the performances in the tests and in educational units, which indicates the need to review the conditions of education and assessment of testing tools. Improve teaching conditions is part of the program and teaching can be proposed in future investigations. This study allows for a more detailed understanding of variables that must be taken into account in the preparation of math lesson plans. Also, it is a step considered by the literature as important for training teachers. Reviewing the implementation of planned lessons can also be an important aspect to be investigated by future research.
Program for lesson planning in elementar school mathematics
Keywords: Educação matemática; Formação de professores; Programação de ensino; Análise do comportamento; Ensino fundamental; Mathematical education; Teacher development; Learning programming; Behavior analysis; Basic education; CIENCIAS HUMANAS::PSICOLOGIA